Wage Inequality in a Burdett-Mortensen World - Lawrence Uren; Gabor Virag (Hungarian Academy of Sciences, Institute of Economics, 2005)
This paper examines the development of wage inequality in the context of a Burdett- Mortensen (1998) model that is extended to incorporate worker heterogeneity through skill requirements in the production process. In this environment, wage dispersion is a natural consequence of firms pursuing different wage strategies as well as a result of worker and firm production heterogeneity. Changes in the wage distribution are then explained by changes in the productivity of heterogeneous firms. The resulting change in theoretical steady state wage distributions as a result of changes in relative productivity is consistent with many of the observed changes in distribution of wages in the US in recent decades. In particular, an increase in the productivity of less efficient firms may reduce between-group inequality while at the same time increase within-group inequality as observed during the 1970s. On the other hand, an increase in productivity of more efficient firms will tend to increase both between- and within-group inequality as observed during the 1980s and 1990s.
Keywords: 330; wage inequality; BM model; skill requirements